The Relationship Between The Characteristics of Pregnant Women And Short Birth Lengh in Bintang Amin Hospital, Bandar Lampung - Ahmad Murtado; Dessy Hermawan; Riyanti Riyanti; Dhiny Easter Yanti; Nova Muhani (Prodi Kedokteran Fakultas Kedokteran Universitas Malahayati, 2026)
Chronic malnutrition, including stunting, is still a serious health concern in Indonesia. Stunting has a 20% tolerance limit defined by the WHO. With a stunting frequency of 27.5% in 2016, Indonesia outperformed Malaysia (17.2%), Thailand (16.3%), and Vietnam (19.4%). According to the SSGI, the prevalence of stunting decreased from 24.4% in 2021 to 21.6% in 2022. A quantitative, cross-sectional study was conducted to determine the relationship between maternal variables and the birth of small babies in 2025.out at Bintang Amin Hospital in Bandar Lampung between March and May of that year.The design employed was descriptive analytic, describing maternal characteristics such as gestational age, maternal height, hemoglobin level, parity, and compliance with iron supplementation, which were then examined in light of the possibility of giving birth to a child with a small birth length. The purpose of this study is to investigate the relationship between the occurrence of short-birth-length newborns at Bintang Amin Hospital and the characteristics of the mother during pregnancy. 55 people in all were included as samples utilizing a total sampling strategy over the study period. The results revealed a significant association between short birth length and maternal age (p = 0.028; OR = 0.211), hemoglobin levels (p = 0.006; OR = 5.841), and compliance with Fe supplementation (p = 0.004; OR = 7.636). The most dominant factor was Fe supplementation compliance, with an OR of 5.812 (95% CI: 1.426 – 23.689). Pregnant women are strongly encouraged to consume iron (Fe) tablets completely and in accordance with health professionals’ recommendations, as compliance with Fe supplementation has been shown to lower the chance of giving birth. with short birth length. Iron supplementation should ideally be started from early pregnancy, taken daily at the appropriate time, and accompanied by a nutritious diet to enhance iron absorption.